Angiodysplasia as a cause of gastrointestinal bleeding in childhood. - Uhlig, H; Stephan, S; Deutscher, J; Kiess, W; Richter, T (2004)
UNLABELLED: Whereas in adults angiodysplasia is a frequent cause of gastrointestinal bleeding, in children this disorder is extremely rare. A 7 10/12 year old girl is presented suffering over 3-4 months from mild but recurrent rectal bleeding. Blood count and serum ferritin and transferrin levels were normal. The rectosigmoideoscopy revealed a rectal lesion, which was confirmed histologically as angiodysplasia. Pathological investigation of the biopsies included HE staining and immunohistological staining of endothelial cells with anti-CD34 and anti-von Willebrand factor. A follow-up period of three years revealed spontaneous regression of the angiodysplastic lesion at the rectosigmoideal localisation, which could be confirmed by endoscopy. CONCLUSION: The outcome of the few pediatric patients described in the literature was reviewed. Due to the lack of conclusive understanding of the nature of this extremely rare vascular disorder and the variable outcome described, a wait and see attitude should be assumed in cases of less clinical affection.